La Penetración de la tradición litúrgica catalano-narbonense en el obispado de Palencia en el siglo XI - Rubio Sadia, Juan Pablo (Miscel·lània litúrgica catalana, 2010)
The responsorial from the Breviarium palentinum printed in 1565 shows a clear origin from Narbonne. The reason for this influence cannot be other than the action of bishop-abbot Ponç de Tavèrnoles and the irruption of catalan clerics in the Church of Palencia in 1034, when the bishopric was restored. The importance of this liturgical affinity, unknown until now, involves in our oppinion the introduction ot the Franco- Roman rite in a cathedral in Castile-León nearly fifty years before the celebration of the Concile of Burgos (1080). This allows a more progressive and expanded-intime interpretation of the liturgical transition, with a preparatorial phase that has in the «catalan Palencia» an essential core, and receives the definitive impulse with the foundation of the Cluniac priories of San Isidro de Dueñas (1073) and San Zoilo de Carrión (1076), in the eve of the Burgos assembly.